Cultural tourism and its role in achieving a tourist attraction to the Moroccan imperial cities: Marrakesh city is a model - QAMMOURI , Mustapha (Social Empowerment Journal, 2021)
Morocco is one of the countries that attaches great importance to tourism, due to its important position in the national economy, as cultural tourism is among the oldest Moroccan tourism offers related to the ancient history of Morocco, this made the country with a competitive cultural tourist offer at the international level, as a result of the state’s policies directed at restoring monuments Historical and rehabilitation of archaeological sites scattered in the imperial cities, during our article, we will try to take a model of cultural tourism and the extent of its contribution to the events of tourism development in the region of Marrakesh-Safi.